Married and Gained Weight: The Role of Gender and Marital Life on Overweight or Obesity Status - Nareta, Auliya; Undarwati, Anna (Journal of Educational, Health and Community Psychology, 2024)
The problem of overweight or obese people is increasing every year. This is due to overeating and reduced physical activity. Being overweight or obese has become a serious problem because currently, no country has been able to reduce the number of overweight or obese. In addition, obesity can also cause cardiovascular disease, diabetes, hypertension, metabolic syndrome, depression, and even worse can cause death. Therefore, this study will examine overweight or obesity in the context of marriage. This study uses quantitative research with the measurement using two-way Anova and generalized linear model. This study used the Dutch Eating Behaviour Questionnaire (DEBQ) scale using a Likert scale with a score range of 1 (never) to 5 (very often) for responses. The results of this study explained that female participants were more likely to be overweight or obese than male participants. When viewed based on marital status, both married men and women are more likely to be overweight or obese than those who are not married. It's just that when viewed based on gender and status married women are more likely to experience overweight or obesity. Keywords: Overweight; obesity;gender; married